Structure and dynamics of the community of periphytic algae in a subtropical reservoir (state of São Paulo, Brazil) - Taniwaki, Ricardo Hideo [UNESP]; Borghi, Tatiana Cintra; Magrin, Albano Geraldo Emílio; Calijuri, Maria do Carmo; Bottino, Flávia; Moschini-Carlos, Viviane [UNESP] (FapUNIFESP (SciELO), 2013)
Much remains to be learned about biological diversity, which constitutes a valuable natural resource. Due to the pressure that human activity has put on natural resources, biodiversity has been reduced, often unbeknownst to those responsible for that activity. Therefore, we aimed to perform a quantitative and qualitative analysis of periphytic algae in the Itupararanga reservoir, correlating the results with the physical and chemical characteristics of the water, as well as with climatic conditions. To that end, five samples were collected at four sampling stations in the Itupararanga reservoir during the year 2010. Aquatic macrophytes were collected with a 156-cm2 frame, and the periphytic algae were scraped free of the macrophytes with a brush. Samples were fixed in formaldehyde and Lugol's solution for the qualitative and quantitative analyses, respectively. We identified 156 taxa belonging to eight classes, and the overall density was 10,200-171,800 individuals/mm2. The taxonomic composition and abundance of periphyton were found to be dependent on spatial and temporal factors, such as the type of substrate and the characteristics of the sampling site, as well as seasonal variations in the chemical and physical properties of the water.
Keywords: Detrended correspondence analysis; Macrophytes; Periphyton; Principal components analysis; Water quality